A Novel Framework for Inner-Outer Sustainability Assessment - Kira J. Cooper; Robert B. Gibson (Challenges, 2022)
Calls for systemic transformations have become prevalent throughout sustainability discourse. Increasingly, these calls point towards consciousness expanding practices and interventions, such as mindfulness, to support the development of individual understandings, skills, and capacities that are conducive to more sustainable ways of being and doing. The growing interest in leveraging inner capacities, including mindsets, worldviews, values, and beliefs for sustainability transformations emerges from concerns that conventional approaches are failing to align social and ecological systems towards long-term viability. Interest in these consciousness-driven transformations is spreading, particularly in governments and prominent organisations. Tempering this enthusiasm are concerns that untethered from moral and ethical guidelines as well as caring understanding of local and global prospects for lasting wellbeing, mindfulness programs, workshops, and interventions for inner transformation can inadvertently strengthen unsustainable systems and deepen inequities. Accordingly, this paper presents an exploratory assessment framework to increase understandings of how events focused on interventions for inner transformation align with broad sustainability requirements. Findings from application of the framework should help to elucidate how these offerings can disrupt normative ways of thinking and doing, and in turn, positively influence multi-scalar transformations. Furthermore, use of the assessment process to plan and/or evaluate inner development offerings is anticipated to help strengthen progress towards sustainability and reduce adverse trade-offs that might undermine positive systemic transformations.